Desain Media Pembelajaran Struktur Bumi Dan Batuan Berbasis Interaktif - Fitro Nur Hakim; Eko Wahyu Wibowo (STEKOM PRESS, 2023)
The development of information technology brought a lot of impact on education, both positive and negative impacts. One positive impact is involved the development of instructional media for school students. This study takes a case study at SMK Grafika Bakti Nusantara Semarang.Proses data collection using interviews, observation and literature study. Dsesign in this study using ADDIE method approach. Results of this research is an interactive multimedia used by students to study the structure of earth and rock interactively. The animation and music will help the students to reduce boredom in the learning process. In learning media earth and rock structure is also equipped with a quiz that can be accessed directly by students to measure the level of students' understanding of the material structure of the earth and rocks are studied. Material quiz built using database that allows administrators to update the material question.